Highly Enantioselective Iron‐Catalyzed cis‐Dihydroxylation of Alkenes with Hydrogen Peroxide Oxidant via an FeIII‐OOH Reactive Intermediate. (26th July 2016) - Zang, Chao; Liu, Yungen; Xu, Zhen‐Jiang; Tse, Chun‐Wai; Guan, Xiangguo; Wei, Jinhu; Huang, Jie‐Sheng; Che, Chi‐Ming
Abstract: The development of environmentally benign catalysts for highly enantioselective asymmetric cis ‐dihydroxylation (AD) of alkenes with broad substrate scope remains a challenge. By employing [Fe II (L)(OTf)2 ] (L= N, N ′‐dimethyl‐ N, N ′‐bis(2‐methyl‐8‐quinolyl)‐cyclohexane‐1, 2‐diamine) as a catalyst, cis ‐diols in up to 99.8 % ee with 85 % isolated yield have been achieved in AD of alkenes with H2 O2 as an oxidant and alkenes in a limiting amount. This "[Fe II (L)(OTf)2 ]+H2 O2 " method is applicable to both ( E )‐alkenes and terminal alkenes (24 examples >80 % ee, up to 1 g scale). Mechanistic studies, including 18 O‐labeling, UV/Vis, EPR, ESI‐MS analyses, and DFT calculations lend evidence for the involvement of chiral Fe III ‐OOH active species in enantioselective formation of the two C−O bonds.